The Relationship between Psychological Empowerment and Work Life Balance - Claudia Cindry Dorotea (International Journal on Social Science, Economics and Art, 2020)
This research aims to examine relation between psychological empowerment and work life balance on employee at Kantor Bupati Kabupaten Serdang Bedagai, Sei Rampah, Sumatera Utara. This research used quantitative method with correlation type. This research used the simple random sampling technique in data collection with 186 employees. Data were collected by using scale of psychological empowerment based on Spreitzer’s theory (1995) and scale of work life balance based on Fisher’s theory (2009). This research has shown that there is a positive correlation between psychological empowerment and work life balance. In conclusion, employee who had felt more empowered theirselves psychologically, they will had more work life balance.